Heterogeneous economic evolution: A different view on Darwinizing evolutionary economics - Jack Vromen (Max Planck Institute of Economics, 2010)
Inspired by Peter Godfrey-Smith's book Darwinian Populations and Natural Selection (2009), the paper seeks to develop a view on Darwinizing evolutionary economics that differs from the view espoused in Hodgson and Knudsen project of Generalized Darwinism. It is argued that on Hodgson and Knudsen's view Darwinism is understood on such a high level of abstraction and generality that it is emptied from virtually all content and substance. Only on the basis of a very abstract, general and broad understanding of the Darwinian principles of variation, selection and replication can Hodgson and Knudsen's claim be defended that any acceptable explanation must invoke the three Darwinian principles. The price they have to pay for this, however, is that the Darwinian principles provide little, if any, heuristic guidance to further theory construction. By contrast, on the alternative view developed in the paper Darwinism has a definite content. On the alternative view not all economic processes are Darwinian in kind: some economic processes appear as paradigmatically Darwinian, others only as minimally Darwinian and yet others as not Darwinian at all.
urn:nbn:de:gbv:27-20110628-145852-0
Keywords: 330; Bioökonomik; Evolutionsökonomik